Neuroprotection by the Ketogenic Diet: Evidence and Controversies - Gough, Sarah M.; Casella, Alicia; Ortega, Kristen Jasmin; Hackam, Abigail S. (Frontiers in Nutrition, 2021)
The ketogenic diet (KD) is a high fat low carbohydrate diet that has been used for decades as a non-pharmacologic approach to treat metabolic disorders and refractory pediatric epilepsy. In recent years, enthusiasm for the KD has increased in the scientific community due to its potential neuroprotective properties based on evidence that the diet reduces pathology and improves various outcome measures in animal models of neurodegenerative disorders, including multiple sclerosis, stroke, glaucoma, spinal cord injury, retinal degenerations, Parkinson’s disease and Alzheimer’s disease. Clinical trials also suggest that the KD improved quality of life in patients with multiple sclerosis and Alzheimer’s disease. Furthermore, the major ketone bodies BHB and ACA are now known to have direct effects on specific inflammatory proteins, transcription factors, reactive oxygen species, mitochondria, epigenetic modifications and the composition of the gut microbiome. Neuroprotective benefits of the KD are likely due to a combination of these cellular processes and other potential mechanisms that are yet to be confirmed experimentally. This review provides a comprehensive summary of current evidence for the effectiveness of the KD in humans and preclinical models of various neurological disorders, describes molecular mechanisms that may contribute to its beneficial effects, and highlights key controversies and current gaps in knowledge.